THE IMPACT OF FLIPPED CLASSROOM ON STUDENT ACADEMIC FOR SPEAKING SKILLS - Nasywa Kamilah; Farah Fadhilah; Nazwa Khalifatunnisa; Naf’an Tarihoran (Review of International Journal Education and School Leadership, 2026)
The purpose of this study was to examine how the flipped classroom paradigm affects students' speaking skills and academic achievement. This study used a quantitative research methodology to investigate how the flipped classroom approach impacts students' perceptions and learning experiences in speaking classes. A total of 110 students who had used this learning style participated in the study. A fifteen-item Likert-scale questionnaire was used to collect data on learning experiences, classroom interactions, speaking confidence, and technique efficacy. Descriptive statistics, such as percentages, means, medians, and standard deviations, were used to analyze the collected data. According to the study results, the majority of students had positive opinions about the flipped classroom approach, particularly in terms of better comprehension of speaking materials, higher engagement in class, and increased confidence in speaking. Furthermore, it was found that the flipped classroom resulted in a more dynamic and student-centered learning environment. Consequently, the study found that the flipped classroom approach successfully increased students' motivation to learn English and their speaking skills. The results also showed that language learning outcomes can be significantly improved by combining technology with interactive learning techniques.